If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x + -2 = 2x + -2 Reorder the terms: -2 + 1x = 2x + -2 Reorder the terms: -2 + 1x = -2 + 2x Add '2' to each side of the equation. -2 + 2 + 1x = -2 + 2 + 2x Combine like terms: -2 + 2 = 0 0 + 1x = -2 + 2 + 2x 1x = -2 + 2 + 2x Combine like terms: -2 + 2 = 0 1x = 0 + 2x 1x = 2x Solving 1x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1x + -2x = 2x + -2x Combine like terms: 1x + -2x = -1x -1x = 2x + -2x Combine like terms: 2x + -2x = 0 -1x = 0 Divide each side by '-1'. x = 0 Simplifying x = 0
| 48*10^18/4*10^4 | | 12/3/11/3 | | 2x+3/5=x | | x-9/8=4/5 | | x-3(2x+3)=11 | | 82-2x=16+20 | | 5/3/11/3 | | 136-4x=23x+16 | | x(3x-1)(3x+2)=0 | | 11a-3b=20 | | 48x10^14/4x10^4 | | F(x)=-3x^2-14x+24 | | 3/2d=27 | | 9=-2(9-3) | | V=18(8)(2) | | 3a-2=9 | | 9/5t=27 | | 5s^4+22s^2t+8t^2= | | V=-2000t+15000 | | 3/7t=18 | | -3r+4(r+2)=11 | | 2.68-1.44= | | 2m=x | | 2/5y=22 | | 8x+7-p-2p= | | A=1/2(20)(12) | | 3a-2a=9 | | 1/2(20)(12) | | 18=30-2logx | | 5(3m-2)+10=25 | | 10x^2+28x+14= | | 2*3.14*7.08=c |